A internacionalização das empresas brasileiras: o BNDES e o incentivo aos grupos JBS e MARFRIG - Oliveira, Alessandro Francisco Trindade de (2015)
In the 2000s we observed that Brazilian investments abroad had a substantial increase in relation to other periods, and happen by several reasons that allowed a favorable condition both internally and externally. The Geograph in its genesis is concerned to analyze some of the spaces transformation factors, so our concern was also focused on the discussion of how Brazilian companies established abroad would be part of a change in the economic o and political order in the period. Seeking to preliminary information respecting national companies investing abroad, we find that the meat industry was highlighted with two large multinationals in the industry: JBS and Marfrig Group. From this we understand what strategies these groups looking for international expansion. We found that in addition to entrepreneurship, both had broad access to public funding from the BNDES and internal and external conditions favorable. Thus we see that the formation of large Brazilian multinationals is still an ongoing process, but already represents a small change to the national business dynamics, acting similarly to other countries, especially when we analyze the current processes in other emerging and developed nations.